Peningkatan Kreativitas Berbahasa Melalui Kegiatan Pentas Kreasi Bahasa dan Sastra pada Siswa SMP Negeri 15 Surabaya - Niar Martin Fernanda; Syafa Husada; Ana Sirotul Mubaroh; Ahmad Khimas Adil; Khusnul Khotimah (Jurnal Pemberdayaan Masyarakat dan Komunitas, 2024)
Indonesian is the language used daily by Indonesian people and functions as the official language in formal activities. This language is also the main medium in the world of education and is taught at all levels of school, from kindergarten, elementary school, middle school, high school, to university. One important aspect in mastering Indonesian is language skills, which can be measured through various training and competitions. This activity encourages teaching assistance students to organize an event to commemorate Language and Literature Month at SMP Negeri 15 Surabaya, where they carry out their duties at Trunojoyo Madura University. The aim of this competition is to increase the language creativity of SMPN 15 Surabaya students while providing meaningful and useful experiences through creative performances. The implementation of this activity is carried out through several stages, namely the preparation stage and the implementation stage. The categories of language and literary creation performances that are held include chain poetry performances, storytelling, poetry musicals, stand up comedy, monologues, recital of rhymes and orations. This performance category is designed to increase students' language creativity and literacy interest, especially in the field of Indonesian.